Renal biopsy in the management of lupus nephritis during pregnancy. (February 2015) - Chen, T K; Gelber, A C; Witter, F R; Petri, M; Fine, D M
The differential diagnosis of proteinuria and hematuria in pregnancy is broad and includes active lupus nephritis. Identification of the correct diagnosis often has a profound therapeutic impact on not only the mother but also the fetus. To date, relatively few reports exist on the role of renal biopsy during pregnancy among women with systemic lupus erythematosus (SLE). We present a case series of 11 pregnant women with SLE who underwent a renal biopsy to evaluate a presumptive flare of lupus nephritis. The electronic medical record was retrospectively analyzed for pre-biopsy serum creatinine, proteinuria, hematuria, antinuclear antibodies (ANA), and antibodies to double-stranded DNA (anti-dsDNA); histologic findings on renal biopsy; and the clinical course of each mother and fetus. From 2001 to 2012, 11 pregnant women with SLE flares during pregnancy underwent a renal biopsy at an academic tertiary medical center. At the time of biopsy, median gestational age was 16 weeks (range 9 to 27), median serum creatinine was 0.6 mg/dl (interquartile range 0.5 to 0.9), six (55%) had hematuria, and all had proteinuria >500 mg/24 hours. Proliferative lupus nephritis was found in 10 (91%) of 11 biopsies (five with ISN/RPS Class III; five with ISN/RPS Class IV). All but one individual underwent a change in management guided by information gleaned from renal biopsy. No apparent biopsy-related complications occurred to mother or fetus. Three women elected to terminate their pregnancy; although many factors were involved, the findings on renal biopsy informed the decision-making process. Among the remaining cases, there were three pre-term deliveries, one fetus with complete heart block, one in utero demise, and one maternal death. Renal biopsy is helpful at informing the management of patients with lupus nephritis during pregnancy.